COMPARISON TEST OF FNAA AND AAS METHOD FOR Cu, Cd, Cr, AND Pb ANALYSIS OF CODE RIVER SEDIMENT (INDONESIA) - Sunardi Sunardi; C. Supriyanto (Indonesian Journal of Chemistry, 2008)
Comparison test of Fast Neutron Activation Analysis (FNAA) and Atomic Absorption Spectrometry (AAS) method for analysis of Cu, Cd, Cr, Pb elements in Code river sediment samples has been done. Comparisons of test used Standard Reference materials (SRM) sample, covering the validation test, t test and F test for both method and then these methods were used to analyze the Code river sediment samples. Comparisons test result show that the validity of both method are around 92.69 % to 98.12 % and t test show that there is no significant difference in average concentration, F test of both methods show that there is no difference in accuracy. The analysis  result of Code sediment using FNAA for Cu, Cd, Cr, Pb are (15.41 - 53.92) ppm, (1.82 - 3.66) ppm, (14.72 - 87.28) ppm, (18.23 - 109.31) ppm respectively, while those using AAS method are (13.71 - 51.11) ppm, (1.64 - 3.33) ppm, (12.81 - 86.75) ppm, (15.74 - 105.53) ppm, respectively. Statistic result test using ANOVA method showed that the concentration of Cr are not significantly differences within sampling locations, while those for Cd, Cr, Pb show a significant difference within sampling location